RELIGIOUS AND POLITICAL ROLES OF THE CHURCH OF THE HOLY SEPULCHRE - Chen, Jeffrey (PEOPLE: International Journal of Social Sciences, 2020)
This article examines changes to the role of the Church of the Holy Sepulchre (CHS) from its construction to the Latin Kingdom and argues that these changes reflect shifts in Christian perception of sacred space. When it was first built, the CHS was only a monument to the profound event of Christ’s resurrection. During the Heraclian dynasty of the Byzantine Empire, the very structure of the CHS became sacred and Jerusalem became revered as the city of the Holy Sepulchre. As Muslims conquered Jerusalem in the late 7th century AD, the CHS became increasingly emblematic of Christianity itself. Eventually, the CHS was used as a rallying cry to incite European Christians into a crusade. During the Crusader Period, the CHS was transformed into a symbol of Frankish rule. As pilgrims became more intimate with the CHS, Jerusalem’s sacred geography was expanded from only the CHS to include sites encompassing all aspects of Jesus’s life. With these changes to the roles of the CHS, Christians went from originally distrusting sacred space, to embrace the church as their sole axis mundus (sacred space), to accepting the presence of multiple axis mundi on earth; the CHS was among them.